Estudos moleculares da localização gênica da proteína P21 de Trypanosoma cruzi em diferentes cepas - Souza Neto, Cecílio Purcino da Silva (2014)
P21 protein was recently characterized, being secreted by all developmental forms of the parasite and plays a role during the invasion of non- phagocytic cells by metacyclic trypomastigotes and extracellular amastigotes. P21 can induce the polymerization of the actin cytoskeleton of the host cell. In addition, P21 has the ability to enhance the phagocytic capacity of macrophages by a mechanism dependent protein binding to the chemokine receptor CXCR4. Studies of genotype and phenotype of T. cruzi showed that this species is represented by a very heterogeneous population This diversity is related to their drug susceptibility, virulence, antigenicity, and variations in their molecular karyotype. In 2005 was completed the sequencing of clone CL Brener genome. In 2009, the genome was organized in 41 homologous pairs, with size between 78kb and 2.3 Mb, provisionally called chromosomes or TcChr. T. cruzi, in general, has a plastic genome size. Its chromosome may vary among different strains of the parasite, with bands of 450 kb to 3 Mb. Studies suggested the occurrence of rearrangements during the development of this parasite. The possibility for such rearrangements is the occurrence of several repeated regions of DNA of this parasite or the final chromosomal structure of its chromosomes, such as telomeric or subtelomeric regions. In the present study, we found that isolates of group Tc VI, Tc II and Tc I ( CL Brener , CL , Y and G ) kept its sequence syntenic, but with a region of rearrangements, but when observed its isolated location in group TcV ( strain 115), we verified that not only had cromossome 22 size reduction as well as its size corrected forming equal chromosomes. The present study showed that even clonal reproduction occurring in T. cruzi, it could not prevent variations ion its genome. These variations may promote gain or loss of genomic content. Thus, we can conclude that: P21 protein is unique to T. cruzi and it can be considered species-specific, so it could be used as a molecular marker for T. cruzi taxon. Genomic environment of P21 denoted an important and heterogeneous environment. The chromosome where P21 is located undergoes rearrangements as observed to the studied strains.